2010
DOI: 10.1056/nejmoa1002853
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Sensor-Augmented Insulin-Pump Therapy in Type 1 Diabetes

Abstract: In both adults and children with inadequately controlled type 1 diabetes, sensor-augmented pump therapy resulted in significant improvement in glycated hemoglobin levels, as compared with injection therapy. A significantly greater proportion of both adults and children in the pump-therapy group than in the injection-therapy group reached the target glycated hemoglobin level. (Funded by Medtronic and others; ClinicalTrials.gov number, NCT00417989.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
601
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 819 publications
(647 citation statements)
references
References 11 publications
27
601
2
17
Order By: Relevance
“…A recent meta-analysis confirms these results [27] and a Cochrane review appeared a short while ago [28]. The improvement is observed at 3 months [23] and maintained at 6 months [24], 12 months [26,29,30] and 18 months [24], the maximum follow-up of the studies to date. The improvement is observed whatever the initial level of HbA 1c is, whether the patient uses a pump or multiple daily injections [21] and however long a pump has previously been used by a particular patient.…”
Section: Description Of the Technologymentioning
confidence: 75%
See 3 more Smart Citations
“…A recent meta-analysis confirms these results [27] and a Cochrane review appeared a short while ago [28]. The improvement is observed at 3 months [23] and maintained at 6 months [24], 12 months [26,29,30] and 18 months [24], the maximum follow-up of the studies to date. The improvement is observed whatever the initial level of HbA 1c is, whether the patient uses a pump or multiple daily injections [21] and however long a pump has previously been used by a particular patient.…”
Section: Description Of the Technologymentioning
confidence: 75%
“…The information provided by CGM is constantly accessible and permits the patient to adjust daily insulin dosing, avoid unnoticed high or low glucose levels and thus improve his glucose control. In the studies, CGM significantly reduces HbA 1c by about 0.5% as compared to intermittent SMBG, provided that the patient uses CGM at least 40% of the prescribed time [19,[23][24][25][26]. The results of these studies are detailed in Table 2.…”
Section: Description Of the Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis done of 15 randomized trials of CSII versus multiple daily injections found no significant difference in severe or nocturnal hypoglycemia between the two therapies [21]. In a newly published multicenter randomized controlled trial of glucose sensoraugmented CSII therapy versus a regimen of multiple daily insulin injections, CSII produced a significantly lower glycated hemoglobin level at 1 year, with no significant difference in the rate of severe hypoglycemia between the two groups [22]. The Food and Drug Administration has studied medical device adverse event reports for insulin pumps in adolescents over a 10-year period, revealing 13 deaths.…”
Section: What Are the Advantages And Risks Of Insulin Pump Therapy?mentioning
confidence: 99%